Mu`'am shuyukh al-hafiz al-Dimyati min bidayat al-kitab ila nihayat al-juz' al-khamis : dirasah wa-tahqiq wa-tahdhib = Mu'jam suyukh al-hafiz al-Dimyati from the beginning of the book until chapter five : an analysis, critique and summarization / Ibrahim Najm Abdulrahman - Abdulrahman, Ibrahim Najm (2012)
This thesis is an analysis and a critique of Mu’jam Suyukh al-Hafiz al-Dimyati from the beginning until chapter five. The thesis is based on a unique manuscript written in an elegant style by its author, al-Hafiz al-Dimyati, in the 7th century, 800 years back. The manuscript includes names of prominent scholars from the 7th century. It also includes many marwiyat, useful information on Hadiths, historical events and lines of poetry. The thesis was very precise in referring the scholars to the main sources of biography and figurative scholars. The total of scholars stated in this thesis (i.e., the five chapters of the Mu’jam) is (146) scholars. The Hadiths included in the study were also judged, as being sound or weak, according to the analysis and critique of scholars. The marwiyat and lines of poetry were, as well, analyzed and referred to according to their sources. The thesis devotes a whole chapter to the study of the biography of al-Hafiz al-Dimyati. The study is deep and provides useful and new information gathered from reading the whole Mu’jam of al-Dimyati and tracing biography references. The chapter was outlined as follows: the life of al-Dimyati, al-Dimyati’s biography, al-Dimyati’s raising up, al-Dimyati’s scholarly trips, al-Dimyati’s scholars, al-Dimyati’s students, al-Dimyati’s scholarly status, positions held by al-Dimyati, compliment of scholars on al-Dimyati and al-Dimyati’s writings. The thesis, then, discusses the methodology of al-Dimyati in his Mu’jam, divided into three sections: the Hadith aspect, the historical aspect and the poetry aspect. Thus, all which is related to these three sections is included.